Analisis Rasio Keuangan Yang Mempengaruhi Pertumbuhan Sisa Hasil Usaha Pada Koperasi Simpan Pinjam (Ksp) Mitra Usaha Blora Periode 2015-2021 - Azzadah, Ayu; Novandalina, Arini (Jurnal Rekognisi Akuntansi, 2023)
This study aims to identify the influence of CR, DAR, TATO, and NPM on the growth of remaining business results at KSP Mitra Usaha Blora from 2015 to 2021. The population of this study is the financial statements of KSP Mitra Usaha Blora, with the sample consisting of the financial statements of RAT KSP Mitra Usaha Blora from 2015 to 2021. The independent variables are CR, DAR, TATO, and NPM, while the dependent variable is the remaining business results. Data was collected using documentation methods, then analyzed using descriptive statistical analysis, classical assumption tests (normality, multicollinearity, heteroscedasticity, autocorrelation), multiple linear regression, and hypothesis testing (t-test, coefficient of determination test). The results of the study indicate that CR, DAR, and TATO have a significant effect on the growth of remaining business results, while NPM does not have a significant effect.